المفاوضة الجماعية وسيلة بديلة لتسوية منازعات العمل دراسة مقارنة - محمود, أ. م. د. دلاوه ر صالح (Sulaimani Journal for Humanities, 2023)
Collective negotiations are the dialogue and discussions that take place between workers and employers or the unions that represent them concerning the conflict that has arisen in the field of work having a negative impact on the performance of work. After the establishment of trade unions and the change of status of workers from slaves to a free human being. Subsequently, collective work negotiations appeared as a friendly and alternative way for the judiciary to resolve labour disputes, in order to improve work conditions and increase wages in order to provide an acceptable measure of living for workers. The scope of negotiations is defined by workers and employers whether at the state level or any other levels. International and Arab labour organizations, as well as national legislation are concerned with collective labour negotiations.
Keywords: Collective Negotiations; Alternative Dispute Resolution; Collective Labor Disputes